1993
DOI: 10.1037/0022-006x.61.5.743
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine delivery kinetics and abuse liability.

Abstract: It is well established that nicotine meets all criteria of a highly addictive drug. However, as recognized by the U.S. surgeon general, the nicotine delivery system itself is an important determinant of the toxic and addictive effects engendered by nicotine use. Therefore, altering the form of nicotine dosing may allow for selective therapeutic action in efforts to develop safer and less addictive nicotine replacement therapies. While it is the case that initial tobacco use often escalates to compulsive use ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
255
2
7

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(271 citation statements)
references
References 37 publications
7
255
2
7
Order By: Relevance
“…Previously, we demonstrated differential effects of acute, chronic, and withdrawal from chronic nicotine on contextual fear conditioning in mice. Acute nicotine enhanced contextual fear conditioning; however, a dose of chronic nicotine that produced similar plasma nicotine levels (and was within the range observed in smokers (Benowitz, Porchet, & Jacob, 1989;Henningfield, & Keenan, 1993)) had no effect, suggesting the development of tolerance. Furthermore, contextual fear conditioning was disrupted in mice withdrawn from chronic nicotine treatment (Davis, James, Siegel, & Gould, 2005).…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Previously, we demonstrated differential effects of acute, chronic, and withdrawal from chronic nicotine on contextual fear conditioning in mice. Acute nicotine enhanced contextual fear conditioning; however, a dose of chronic nicotine that produced similar plasma nicotine levels (and was within the range observed in smokers (Benowitz, Porchet, & Jacob, 1989;Henningfield, & Keenan, 1993)) had no effect, suggesting the development of tolerance. Furthermore, contextual fear conditioning was disrupted in mice withdrawn from chronic nicotine treatment (Davis, James, Siegel, & Gould, 2005).…”
Section: Introductionmentioning
confidence: 65%
“…The selection of this dose of nicotine was based on previous research demonstrating that withdrawal from chronic nicotine administration of this dose will produce impairments in contextual fear conditioning in C57BL/ 6 mice, and this dose produces plasma nicotine levels comparable to what is observed in smokers (Benowitz et al, 1989;Davis et al, 2005;Henningfield & Keenan, 1993). Pumps were removed 12 days after pump implantation.…”
Section: Drug Administration and Experimental Designmentioning
confidence: 99%
“…However, contextual conditioning is not altered by a dose of chronic nicotine that produces the same plasma nicotine levels as the acute dose that produces enhancement, suggesting the development of tolerance [30]. It is important to note that these plasma nicotine levels were within the range observed in smokers [5,64]. Additionally, withdrawal from chronic nicotine disrupts contextual but not cued conditioning [2,33,30,132,133], and this impairment in contextual learning can be ameliorated by nicotine replacement and by the smoking cessation drugs bupropion and varenicline [30,132,135].…”
Section: Nicotinic Acetylcholine Receptors: Animal Researchmentioning
confidence: 77%
“…For contextual fear conditioning, pumps were loaded with a 6.3 mg/kg/day (freebase weight) nicotine solution. This dose was chosen based on prior research which demonstrated that 6.3 mg/kg/day nicotine produced plasma nicotine levels of approximately 13.00 ng/ml [13], which is within the range of plasma nicotine found in smokers, approximately 10-50 ng/ml [35], and based on previous research in our lab showing that withdrawal from 6.3 mg/kg/day chronic nicotine produces significant deficits in background contextual fear conditioning [16,13,65]. For pre-pulse inhibition, pumps were loaded with nicotine (6.3 or 12.6 mg/kg/day) or saline solutions.…”
Section: Drugs and Administrationmentioning
confidence: 99%